Current Evidence Linking Polyunsaturated Fatty Acids with Cancer Risk and Progression - Azrad, Maria; Turgeon, Chelsea E.; Demark-Wahnefried, Wendy (Frontiers in Oncology, 2013)
There is increasing evidence that polyunsaturated fatty acids (PUFAs) play a role in cancer risk and progression. The n-3 family of PUFAs includes alpha-linolenic acid (ALA), eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) while the n-6 family includes linolenic acid (LA) and arachidonic acid (AA). EPA and DHA are precursors for anti-inflammatory lipid mediators while AA is a precursor for pro-inflammatory lipid mediators. Collectively, PUFAs play crucial roles in maintaining cellular homeostasis, and perturbations in dietary intake or PUFA metabolism could result in cellular dysfunction and contribute to cancer risk and progression. Epidemiologic studies provide an inconsistent picture of the associations between dietary PUFAs and cancer. This discrepancy may reflect the difficulties in collecting accurate dietary data; however, it also may reflect genetic variation in PUFA metabolism which has been shown to modify physiological levels of PUFAs and cancer risk. Also, host-specific mutations as a result of cellular transformation could modify metabolism of PUFAs in the target-tissue. Clinical trials have shown that supplementation with PUFAs or foods high in PUFAs can affect markers of inflammation, immune function, tumor biology and prognosis. Preclinical investigations have begun to elucidate how PUFAs may mediate cell proliferation, apoptosis and angiogenesis and the signaling pathways involved in these processes. The purpose of this review is to summarize the current evidence linking PUFAs and their metabolites with cancer and the molecular mechanisms that underlie this association. Identifying the molecular mechanism(s) through which PUFAs affect cancer risk and progression will provide an opportunity to pursue focused dietary interventions that could translate into the development of personalized diets for cancer control.